2015
DOI: 10.1515/hf-2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of brown rot decay resistance in phenol-formaldehyde-modified wood: resistance to Fenton’s reagent

Abstract: The mode of action of phenol-formaldehyde (PF)-modified wood has been investigated with respect to its resistance to brown rot decay. The Fenton reaction is assumed to play a key role in the initial brown rot decay. Pine microveneers were modified to various weight percent gains (WPG) with low molecular weight PF and exposed to a solution containing Fenton's reagent. The mass loss (ML) and tensile strength loss (TSL) as well as the decomposition of hydrogen peroxide within the incubation time decreased with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…One reason might be that the iron ions are hindered from penetrating the cell wall matrix of acetylated wood due to a reduced pore size by cell wall bulking. This theory is supported by studies that found a resistance to Fenton's reagent of acetylated wood [35] and phenol-formaldehydemodified wood [36]. Compared to the mere deposition in the lumen, iron uptake into the cell wall seems to promote its oxidation rate, reduce its loss by washing out, and increase its visibility as a colorant.…”
Section: Discussionmentioning
confidence: 84%
“…One reason might be that the iron ions are hindered from penetrating the cell wall matrix of acetylated wood due to a reduced pore size by cell wall bulking. This theory is supported by studies that found a resistance to Fenton's reagent of acetylated wood [35] and phenol-formaldehydemodified wood [36]. Compared to the mere deposition in the lumen, iron uptake into the cell wall seems to promote its oxidation rate, reduce its loss by washing out, and increase its visibility as a colorant.…”
Section: Discussionmentioning
confidence: 84%
“…Once a satisfactory method has been determined, solute exclusion should be used in future studies to investigate cell wall nanopore accessibility for other chemical modifications. Additionally, the experiment could be performed with probe solutions of chemicals known to be involved in CMF degradation, similar to the work of Hosseinpourpia and Mai [91,102,117] involving iron ion uptake in modified wood.…”
Section: Nanopore Blockingmentioning
confidence: 99%
“…The reactions caused by the FR enable penetration of hydrolytic enzymes, which render polysaccharide metabolism by the fungi possible (Goodell et al 1997;Arantes et al 2012). To keep up redox cycling, the ferric ions, formed during the FR, must be reduced, which may occur via reaction with wood extractives, free phenolic groups in lignin (Hosseinpourpia and Mai 2016) and demethylated lignin (Xu and Goodell 2001), or by fungal phenolic chelators (Goodell et al 1997).…”
Section: Introductionmentioning
confidence: 99%